HUBUNGAN FAKTOR-FAKTOR POLA ASUH ORANG TUA DENGAN KONSEP DIRI ANAK USIA PRA SEKOLAH DI PAUD INSPIRASI GANESA DESA AMERTHA SARI BOLAANG MONGONDOW - Drova Grano Manorek; Vandry Draivon Kallo; Mega Amelia Lumingkewas (JURNAL ILMIAH KESEHATAN MANADO, 2024)
Parenting patterns are parenting patterns that apply in the family, interactions between parents and children during parenting activities. Parenting activities are carried out by educating, guiding, providing protection and supervision of children. The aim of the research is to analyze the relationship between Factors in Parenting Patterns and the Self-Concept of Pre-School Children in Preschool Inspiration Ganesa Amertha Sari Village. This research is quantitative research using a descriptive analytical approach, namely the relationship between two variables in a situation or group of subjects. The sampling technique uses total sampling where the number of samples is the total population, namely 30 respondents.The results of the study using the chi-square test showed a relationship between the parent's age factor and the child's self-concept showing significant results of 0.000 < 0.05, the parent's gender factor on the child's self-concept showing significant results of 0.000 < 0.05, the level of knowledge factor parents regarding the self-concept of pre-school age children at the Ganesa Inspiration Early Childhood Education Center, Amertha Sari Village, did not show significant results, namely 0.064 > 0.05. The results of the research conducted can be concluded that positive parenting styles can produce a positive self-concept in children as well.